Expansion of Genetic Alphabets: Designer Nucleobases and Their Applications - Bag, S. S.; Banerjee, A.; Sinha, S. (Synlett, 2024)
All living things use DNA and RNA to store, retrieve, and transmit their genetic information. The complementary Watson–Crick nucleobase-pairs (A/T and G/C base-pairs), have been documented for years as being essential for the integrity of the DNA double helix and also for replication and transcription. With only four poorly fluorescent naturally occurring nucleic acid bases (namely A, G, T/U, and C), the extraction of genetic information is difficult. Further, the chemical diversity of DNA and RNA is severely limited. Deoxyribose/ribose-phosphate backbones also constrain DNA and RNA characteristics and have poor chemical and physiological stability, which significantly restricts the practical applications of DNA and RNA. Over the years, extensively modified nucleobase pairs with novel base-pairing properties have been synthesized. Such designer nucleobases, serving as an expanded genetic alphabet, have been used for the design and synthesis of DNA and RNA analogues with tailored informational/functional properties. Recent developments in the production of synthetic unnatural base pairs pave the way for xenobiology research and genetic alphabet expansion technology. In this review, we present a brief history of the development of several hydrogen- and non-hydrogen-bonded unnatural base pairs and their applications. We also highlight our work in designing and synthesizing a new class of triazolyl unnatural nucleosides that offer a unique charge-transfer (CT) complexation force towards stabilizing DNA-duplexes when incorporated into short oligonucleotide sequences.
Keywords: genetic alphabet expansion; unnatural nucleobase pairs; triazolyl nucleosides; tetrazolyl nucleosides; fluorescent nucleobases; nucleic acids